Acid mediated sulfonylation of para-quinone methides with tosylmethyl isocyanides for the synthesis of diarylmethyl sulfones - Kumar, Pawan; Kale, Someshwar B.; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2021)
An efficient, hydrochloric acid promoted reaction for the synthesis of diarylmethyl sulfones has been developed via unprecedented 1, 6-conjugate addition reaction of tosylmethyl isocyanide (TosMIC) with para-quinone methides.This catalyst free reaction provides various diarylmethyl sulfones in good to excellent yields in an operationally simple method under metal free conditions. Further transformations of the productsare also demonstrated.
Keywords: 1; 6-Conjugate addition; aromatization; Diarylmethylsulfone; para-Quinonemethide; TosMIC

Metal-free, Tf2NH-catalyzed 1, 6-conjugate addition of imidazopyridine to para-quinone methides: easy access to C3-functionalized triarylmethane imidazopyridine - Khonde, Nilesh S.; Said, Madhukar S.; Sabane, Jagjivan K.; Gajbhiye, Jayant M.; Kumar, Pradeep (Tetrahedron, 2021)
An inexpensive and commercially available Tf2NH-catalyzed 1,6-conjugate addition of imidazopyridine (IMPY) heterocycles to para-quinone methides (p-QMs) is reported. The present transformation provides a diverse class of C3-functionalized triarylmethanes heterocyclic derivatives of imidazopyridine. These metal-free transformations provided a very broad substrate scope of conjugate addition product with a high yield up to 97% within a short duration. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Conjugate addition; Bronsted acid; C3-functionalization; Imidazopyridine; para-Quinone methide